HUBUNGAN BEBAN KERJA FISIK, KUALITAS TIDUR TERHADAP KELELAHAN KERJA PENGEMUDI BENTOR DI KELURAHAN MENTIROTIKU, TORAJA UTARA - Asna Ampang Allo; Putri Yanti (Jurnal Kesehatan dan Kedokteran, 2022)
Unrestricted working time for drivers causes vulnerability to poor sleep quality regulation, and the large number of commuters in the city makes drivers have to work harder and compete with each other to get passengers which tends to cause fatigue for bumpy drivers. Work fatigue is a factor that contributes 50% or more to the occurrence of work accidents. This study aims to analyze the relationship between workload and sleep quality on work fatigue on bentor drivers in Mentiroku Village, Rantepao District, North Toraja. The type of research used is cross sectional using a descriptive approach. Based on the results of the study showed that there was a relationship between workload and work fatigue (p 0.001) and there was a relationship between sleep quality and work fatigue (p 0.009). It is recommended to the bentor driver to immediately get enough rest when the body starts to feel tired, not to force the bentor when the body feels tired to avoid work accidents and regulate sleep patterns well at night.